Composition, cured product, and organic electroluminescence display device
By using a packaging material with high content of inorganic particles in organic EL display equipment, combining photopolymerized compounds and photopolymerized initiator, the problems of humidity barrier and reliability in large equipment are solved, and efficient packaging effect is achieved.
Patent Information
- Application Number
- JP2023511425
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-31
- Filing Date
- 2022-03-29
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2042-03-29
AI Technical Summary
The prior art is difficult to achieve high humidity barrier and long-term reliability in large organic EL display devices.
An encapsulation material with high humidity barrier properties is formed by light irradiation and heat treatment using a combination of 30% inorganic particles, photopolymerized compounds and photopolymerized initiator.
It realizes high humidity barrier and long-term reliability of organic EL display equipment, extending the service life of the equipment.
Smart Images

Figure 0007671842000001 
Figure 0007671842000002 
Figure 0007671842000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition, a cured product, and an organic electroluminescence display device. [Background technology]
[0002] 2. Description of the Related Art In recent years, research into organic optical devices using organic thin-film elements such as organic electroluminescence (organic EL) display elements and organic thin-film solar cell elements has progressed.
[0003] An organic EL display element has a thin film structure in which an organic light-emitting material layer is sandwiched between a pair of electrodes facing each other. Electrons are injected into this organic light-emitting material layer from one electrode and holes are injected from the other electrode, causing the electrons and holes to combine in the organic light-emitting material layer and emit light by themselves. Organic EL display elements have the advantages of good visibility compared to liquid crystal display elements and the like that require a backlight, that they can be made thinner, and that they can be driven with a low DC voltage.
[0004] However, such organic EL display elements have a problem in that when the organic light-emitting material layer or electrodes are exposed to the outside air, their light-emitting characteristics deteriorate rapidly, shortening their lifespan. Therefore, in order to improve the stability and durability of organic EL display elements, a sealing technique that isolates the organic light-emitting material layer and electrodes from moisture and oxygen in the air is essential.
[0005] For example, Patent Document 1 discloses a method for sealing a top-emitting organic EL display element or the like by filling a space between organic EL display element substrates with a photocurable sealant and irradiating the space with light. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2001-357973 A Summary of the Invention [Problem to be solved by the invention]
[0007] In recent years, as organic EL display devices (particularly organic EL televisions) have become larger, there has been a demand for encapsulating materials that can achieve higher moisture resistance and long-term reliability.
[0008] The present invention has been made in view of the above circumstances, and has an object to provide a composition capable of forming a sealing material having excellent moisture resistance and long-term reliability. Another object of the present invention is to provide a cured product of the composition, and an organic electroluminescence display device including a sealing structure formed using the composition. [Means for solving the problem]
[0009] The present invention relates to, for example, the following <1> ~ <18> Regarding. <1> The composition contains a polymerizable compound, inorganic fine particles, and a photopolymerization initiator, the content of the inorganic fine particles being 30% by volume or more, the wavelength being 365 nm, and the irradiation amount being 600 mJ / cm. 2 and allowing to stand at 80°C for 30 minutes, the composition has a curing depth of 100 µm or more. <2> the polymerizable compound has at least one polymerizable group selected from the group consisting of a carbon-carbon double bond and a cyclic ether; <1> The composition described in <3> The inorganic fine particles have a refractive index n2 such that the absolute value (|n1-n2|) of the difference from the refractive index n1 of a polymer of the polymerizable compound is 0.5 or less. <1> or <2> The composition described in <4> The refractive index n2 of the inorganic fine particles is 1.4 or more. <1> ~ <3> 13. The composition according to any one of claims 1 to 12. <5> The average circularity of the inorganic fine particles is 0.7 or more and 1.0 or less. <1> ~ <4> 13. The composition according to any one of claims 1 to 12. <6> The inorganic fine particles include at least one selected from the group consisting of spherical silica and spherical alumina. <1> ~ <5> 13. The composition according to any one of claims 1 to 12. <7> The sum (T0+R0) of the total light transmittance T0 (%) and the total light reflectance R0 (%) per 100 μm thickness is 50% or more. <1> ~ <6> 2. The composition according to claim 1 . <8> The photopolymerization initiator contains a compound represented by the following formula (1): <1> ~ <7> 2. The composition according to claim 1 . [ka] [In formula (1), R 1 represents a hydrogen atom, an optionally substituted alkyl group or an optionally substituted aryl group; X - indicates a monovalent anion. 1 may be the same or different.] <9> The composition further contains a photosensitizer represented by the following formula (2): <1> ~ <8> 13. The composition according to any one of claims 1 to 12. [ka] [In formula (2), R 2 represents an alkyl group which may have a substituent. 2 may be the same or different.] <10> In accordance with JIS Z0208, the moisture permeability is 100g / (m2) per 100μm of thickness measured under conditions of 85℃ temperature and 85% relative humidity. 2 A composition for forming a hardened body within 24 hours, <1> ~ <9> 13. The composition according to any one of claims 1 to 12. <11> The composition is for forming a hardened body having a water absorption rate of 3% or less at a temperature of 85°C and a relative humidity of 85% for 24 hours. <1> ~ <10> 13. The composition according to any one of claims 1 to 12. <12> It is a sealant for organic electroluminescence (EL) display devices. <1> ~ <11> 13. The composition according to any one of claims 1 to 12. <13> It is a sealant for dam formation in the dam-fill method. <1> ~ <12> 13. The composition according to any one of claims 1 to 12. <14> A composition comprising: a polymerizable compound; inorganic fine particles having a refractive index n2 such that the absolute value of the difference between the refractive index n1 of a polymer of the polymerizable compound and n2 (|n1-n2|) is 0.5 or less; and a photopolymerization initiator; wherein the content of the inorganic fine particles is 30 volume % or more, the content of the photopolymerization initiator is 0.3 parts by mass or more relative to 100 parts by mass of the polymerizable compound; and the average circularity of the inorganic fine particles is 0.7 or more and 1.0 or less. <15> <1> ~ <14> 2. A cured product of the composition according to any one of claims 1 to 11. <16> The present invention relates to a display device that includes an organic electroluminescence (EL) display element, and a sealing structure that seals the organic electroluminescence (EL) display element and that is made of a dam and a filler, the dam being: <15> An organic electroluminescence display device comprising the cured product according to claim 1. <17> It is an organic EL TV. <16> The organic electroluminescence display device according to claim 1. Effect of the Invention
[0010] According to the present invention, there is provided a composition capable of forming a sealing material having excellent moisture resistance and long-term reliability. In addition, according to the present invention, there is provided a cured product of the composition, and an organic EL display device including a sealing structure formed using the composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Preferred embodiments of the present invention will now be described in detail.
[0012] The composition of the present embodiment contains a polymerizable compound, inorganic fine particles, and a photopolymerization initiator. In the composition of the present embodiment, the content of the inorganic fine particles is 30 volume % or more. The composition of the present embodiment is irradiated with a wavelength of 365 nm and an irradiation dose of 600 mJ / cm. 2 After being exposed to light at 80°C for 30 minutes, the curing depth is 100 μm or more.
[0013] According to the composition of the present embodiment, a sealant excellent in moisture resistance and long-term reliability can be formed. Therefore, the composition of the present embodiment can be suitably used as a sealant (preferably a sealant for an organic EL display element, particularly preferably a sealant for an organic EL television). In addition, the composition of the present embodiment can be suitably used as a dam-forming sealant for forming a dam in a dam-fill system (a sealing structure consisting of a dam and a fill agent).
[0014] The reason why the composition of the present embodiment exhibits the above-mentioned effect is not necessarily limited, but is considered to be as follows. According to the composition of the present embodiment, a cured body containing a large amount of inorganic fine particles having a low moisture permeability compared to a resin material is formed. In addition, when the content of inorganic fine particles in the composition is increased, the inorganic fine particles tend to hinder light irradiation, and the amount of unreacted monomer (unreacted polymerizable compound) in the cured body tends to increase. However, in the present embodiment, since it has the above-mentioned curing depth, the unreacted monomer is sufficiently reduced by light irradiation during sealing, and the decrease in moisture resistance and reliability caused by the unreacted monomer is suppressed. In other words, in the present embodiment, it is considered that excellent moisture resistance and long-term reliability are realized by forming a composition having a predetermined curing depth while blending sufficient inorganic fine particles.
[0015] In the present embodiment, the polymerizable compound can be said to be a compound having a polymerizable group. The polymerizable compound may be used alone or in combination of two or more kinds.
[0016] The polymerizable compound preferably has at least one polymerizable group selected from the group consisting of a carbon-carbon double bond and a cyclic ether.
[0017] The carbon-carbon double bond may be a radically polymerizable or cationic polymerizable carbon-carbon double bond. Examples of the compound having a carbon-carbon double bond include compounds having a polymerizable group such as a (meth)acryloyl group, a vinyl group, an allyl group, a vinyl ether group, and a vinyl ester group, and among these, a compound having a (meth)acryloyl group ((meth)acrylate compound) is preferred.
[0018] Examples of the (meth)acrylate compound include monofunctional (meth)acrylates having one (meth)acryloyl group, and polyfunctional (meth)acrylates having two or more (meth)acryloyl groups.
[0019] Examples of monofunctional (meth)acrylates include alkyl (meth)acrylates (such as ethyl (meth)acrylate, butyl (meth)acrylate, lauryl (meth)acrylate, etc.), benzyl (meth)acrylate, and ethoxylated-o-phenylphenol (meth)acrylate.
[0020] Examples of polyfunctional (meth)acrylates include alkanediol di(meth)acrylates (such as 1,6-hexanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, etc.), tricyclodecane dimethanol di(meth)acrylate, etc.
[0021] The cyclic ether may be any cyclic ether having cationic polymerizability. Examples of the compound having a cyclic ether include an epoxy compound and an oxetane compound.
[0022] Examples of the epoxy compound include an alicyclic compound having an epoxy group (alicyclic epoxy compound), an aromatic compound having an epoxy group (aromatic epoxy compound), an acyclic compound having an epoxy group (acyclic epoxy compound), etc. One or more of these compounds may be selected and used.
[0023] Examples of the alicyclic epoxy compound include compounds or derivatives thereof obtained by epoxidizing a compound having at least one cycloalkene ring (e.g., a cyclohexene ring, a cyclopentene ring, a pinene ring, etc.) with a suitable oxidizing agent such as hydrogen peroxide or a peracid. Examples of the alicyclic epoxy compound also include hydrogenated epoxy compounds obtained by hydrogenating an aromatic epoxy compound (e.g., a bisphenol A type epoxy compound, a bisphenol F type epoxy compound, etc.).
[0024] Examples of alicyclic epoxy compounds include 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, 3,4-epoxycyclohexylalkyl(meth)acrylate (e.g., 3,4-epoxycyclohexylmethyl(meth)acrylate), (3,3',4,4'-diepoxy)bicyclohexyl, hydrogenated bisphenol A type epoxy resin, and hydrogenated bisphenol F type epoxy resin.
[0025] Among the alicyclic epoxy compounds, those having a 1,2-epoxycyclohexane structure are preferred. Among the alicyclic epoxy compounds having a 1,2-epoxycyclohexane structure, those represented by the following formula (A1-1) are preferred. [ka]
[0026] In formula (A1-1), X represents a single bond or a linking group (a divalent group having one or more atoms).
[0027] The linking group is preferably a divalent hydrocarbon group, a carbonyl group, an ether bond, an ester bond, a carbonate group, an amide bond, or a group in which a plurality of these are linked together.
[0028] X is preferably a linking group. The linking group is preferably a group having an ester bond. An example of a compound having a group having an ester bond as a linking group is 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate.
[0029] From the viewpoint of further improving the moisture resistance of the cured product and further improving the storage stability of the composition, the molecular weight of the alicyclic epoxy compound is preferably 1000 or less, more preferably 450 or less, even more preferably 400 or less, still more preferably 300 or less, and particularly preferably 100 to 280. That is, the molecular weight of the alicyclic epoxy compound may be, for example, 100 to 1000, 100 to 450, 100 to 400, 100 to 300, or 100 to 280.
[0030] When the alicyclic epoxy compound has a molecular weight distribution, the number average molecular weight of the alicyclic epoxy compound is preferably within the above range. In this specification, the number average molecular weight is a value measured by gel permeation chromatography (GPC) under the following measurement conditions, expressed in terms of polystyrene. Solvent (mobile phase): THF Degassing device: ERMA ERC-3310 Pump: JASCO PU-980 ·Flow rate: 1.0ml / min Autosampler: Tosoh AS-8020 Column oven: Hitachi L-5030 ·Set temperature: 40℃ Column configuration: 2 columns of TSKguardcolumnMP(xL) 6.0mmID x 4.0cm (Tosoh Corporation) and 2 columns of TSK-GELMULTIPORE HXL-M 7.8mmID x 30.0cm (Tosoh Corporation), total of 4 columns Detector: RI Hitachi L-3350 Data processing: SIC480 data station
[0031] As the aromatic epoxy compound, any of a monomer, oligomer, and polymer can be used, and examples thereof include brominated bisphenol A type epoxy resins such as tetrabromobisphenol A diglycidyl ether, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, biphenyl type epoxy resins, naphthalene type epoxy resins, fluorene type epoxy resins, novolac phenol type epoxy resins, cresol novolac type epoxy resins, phenyl glycidyl ether, and modified products thereof.
[0032] The aromatic epoxy compound is preferably an aromatic epoxy compound having a bisphenol structure. Among the aromatic epoxy compounds having a bisphenol structure, the compound represented by the following formula (A2-1) is preferred.
[0033] [ka]
[0034] In formula (A2-1), n represents 0 to 30; R 21 , R 22 , R 23 and R 24 each independently represents a hydrogen atom or an optionally substituted alkyl group having 1 to 5 carbon atoms, and n may be 0.1 or more.
[0035] R 21 , R 22 , R 23 and R 24 is preferably a hydrogen atom or a methyl group. 21 , R 22 , R 23 and R 24 may be the same or different, but is preferably the same.
[0036] The aromatic epoxy compound having a bisphenol structure is preferably at least one selected from the group consisting of bisphenol A type epoxy resins and bisphenol F type epoxy resins.
[0037] From the viewpoint of further improving the moisture resistance of the cured body, the molecular weight of the aromatic epoxy compound is preferably 100 to 5000, more preferably 150 to 1000, and further preferably 200 to 450. That is, the molecular weight of the aromatic epoxy compound may be, for example, 100 to 5000, 100 to 1000, 100 to 450, 150 to 5000, 150 to 1000, 150 to 450, 200 to 5000, 200 to 1000, or 200 to 450.
[0038] When the aromatic epoxy compound has a molecular weight distribution, the number average molecular weight of the aromatic epoxy compound is preferably within the above range. In this specification, the number average molecular weight refers to a value calculated in terms of polystyrene measured by gel permeation chromatography (GPC) under the above-mentioned measurement conditions.
[0039] Examples of the acyclic epoxy compound include diglycidyl ethers of alkylene glycols (e.g., ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, etc.), polyglycidyl ethers of polyhydric alcohols (e.g., di- or triglycidyl ethers of glycerin or its alkylene oxide adducts, etc.), diglycidyl ethers of polyalkylene glycols (e.g., diglycidyl ethers of polyethylene glycol or its alkylene oxide adducts, diglycidyl ethers of polypropylene glycol or its alkylene oxide adducts, etc.), etc. Here, examples of the alkylene oxide include ethylene oxide, propylene oxide, etc.
[0040] Examples of the oxetane compound include, but are not limited to, 3-ethyl-3-hydroxymethyloxetane (trade name ARONOXETANE OXT-101, manufactured by Toagosei Co., Ltd.), 1,4-bis[(3-ethyl-3-oxetanyl)methoxymethyl]benzene (OXT-121, manufactured by Toagosei Co., Ltd.), 3-ethyl-3-(phenoxymethyl)oxetane (OXT-211, manufactured by Toagosei Co., Ltd.), di(1-ethyl-(3-oxetanyl))methyl ether (OXT-221, manufactured by Toagosei Co., Ltd.), 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane (OXT-212, manufactured by Toagosei Co., Ltd.), etc. The oxetane compound refers to a compound having one or more oxetane rings in the molecule.
[0041] As the polymerizable compound, a compound having both a carbon-carbon double bond and a cyclic ether can be used. Examples of the polymerizable compound having a carbon-carbon double bond and a cyclic ether include glycidyl (meth)acrylate, epoxycyclohexyl (meth)acrylate, 3-ethyloxetane 3-ylmethyl (meth)acrylate, epoxy-4-vinylcyclohexane, and 3-ethyloxetane 3-ylmethyl vinyl ether.
[0042] Examples of the photopolymerization initiator include a photocationic polymerization initiator, a photoradical polymerization initiator, and a photoanionic polymerization initiator. When the composition of the present embodiment contains a polymerizable compound having a carbon-carbon double bond, the photopolymerization initiator preferably contains a photoradical polymerization initiator. When the composition of the present embodiment contains a polymerizable compound having a cyclic ether, the photopolymerization initiator preferably contains a photocationic polymerization initiator.
[0043] The photocationic polymerization initiator is not particularly limited, and examples thereof include arylsulfonium salt derivatives (e.g., Cyracure UVI-6990 and Cyracure UVI-6974 manufactured by The Dow Chemical Company, Adeka Optomer SP-150, Adeka Optomer SP-152, Adeka Optomer SP-170, and Adeka Optomer SP-172 manufactured by Adeka Corporation, CPI-100P, CPI-101A, CPI-200K, and CPI-201A manufactured by San-Apro Co., Ltd.) 10S, CPI-310B, CPI-310FG, CPI-400S, LW-S1, CibaCure 1190 manufactured by Double Bond, etc.), aryl iodonium salt derivatives (e.g. Irgacure 250 manufactured by Ciba Specialty Chemicals, RP-2074 manufactured by Rhodia Japan), allene ion complex derivatives, diazonium salt derivatives, triazine initiators, and acid generators such as other halides.
[0044] Examples of the photocationic polymerization initiator include an onium salt represented by the formula (B-1). [ka] [In formula (B-1), A represents an element of group VIA to group VIIA with valence m, m is 1 to 2, p is 0 to 3, R represents an organic group bonded to A, D is the following formula (B-1-1): [ka] (in formula (B-1-1), E represents a divalent group; G represents -O-, -S-, -SO-, -SO2-, -NH-, -NR'-, -CO-, -COO-, -CONH-, an alkylene or phenylene group having 1 to 3 carbon atoms (R' represents an alkyl group having 1 to 5 carbon atoms or an aryl group having 6 to 10 carbon atoms); and a represents 0 to 5. a+1 E's and a G's may be the same or different.) X - is the onium counterion.)
[0045] The onium ion of formula (B-1) is not particularly limited, and examples thereof include 4-(phenylthio)phenyldiphenylsulfonium, bis[4-(diphenylsulfonio)phenyl]sulfide, bis[4-{bis[4-(2-hydroxyethoxy)phenyl]sulfonio}phenyl]sulfide, bis{4-[bis(4-fluorophenyl)sulfonio]phenyl}sulfide, 4-(4-benzoyl-2-chlorophenylthio)phenylbis(4-fluorophenyl)sulfonium, 4-(4-benzoylphenylthio)phenyldiphenylsulfonium, 7-isopropyl-9-oxo-10-thia-9,10-dihydroanthracen-2-yldi-p-tolylsulfonium, 7-isopropyl-9-oxo-10-thia-9,10-dihydroanthracen-2-yldi-p-tolylsulfonium, and the like. -dihydroanthracen-2-yldiphenylsulfonium, 2-[(di-p-tolyl)sulfonio]thioxanthone, 2-[(diphenyl)sulfonio]thioxanthone, 4-[4-(4-tert-butylbenzoyl)phenylthio]phenyldi-p-tolylsulfonium, 4-(4-benzoylphenylthio)phenyldiphenylsulfonium, 5-(4-methoxyphenyl)thiaanthrenenium, 5-phenylthiaanthrenenium, diphenylphenacylsulfonium, 4-hydroxyphenylmethylbenzylsulfonium, 2-naphthylmethyl(1-ethoxycarbonyl)ethylsulfonium, 4-hydroxyphenylmethylphenacylsulfonium, and octadecylmethylphenacylsulfonium.
[0046] R is an organic group bonded to A. R represents, for example, an aryl group having 6 to 30 carbon atoms, a heterocyclic group having 4 to 30 carbon atoms, an alkyl group having 1 to 30 carbon atoms, an alkenyl group having 2 to 30 carbon atoms, or an alkynyl group having 2 to 30 carbon atoms, which may have a substituent. Examples of the substituent include at least one selected from the group consisting of an alkyl group, a hydroxy group, an alkoxy group, an alkylcarbonyl group, an arylcarbonyl group, an alkoxycarbonyl group, an aryloxycarbonyl group, an arylthiocarbonyl group, an acyloxy group, an arylthio group, an alkylthio group, an aryl group, a heterocyclic group, an aryloxy group, an alkylsulfinyl group, an arylsulfinyl group, an alkylsulfonyl group, an arylsulfonyl group, an alkyleneoxy group, an amino group, a cyano group, a nitro group, and a halogen.
[0047] The number of R is m+p(m-1)+1, and they may be the same or different. Two or more R may be bonded to each other directly or via -O-, -S-, -SO-, -SO2-, -NH-, -NR'-, -CO-, -COO-, -CONH-, an alkylene group having 1 to 3 carbon atoms, or a phenylene group to form a ring structure containing the element A. Here, R' is an alkyl group having 1 to 5 carbon atoms or an aryl group having 6 to 10 carbon atoms.
[0048] Examples of the aryl group having 6 to 30 carbon atoms include monocyclic aryl groups such as a phenyl group, and condensed polycyclic aryl groups such as a naphthyl group, anthracenyl group, phenanthrenyl group, pyrenyl group, chrysenyl group, naphthacenyl group, benzanthracenyl group, anthraquinolyl group, fluorenyl group, naphthoquinone group, and anthraquinone group.
[0049] The aryl group having 6 to 30 carbon atoms, the heterocyclic group having 4 to 30 carbon atoms, the alkyl group having 1 to 30 carbon atoms, the alkenyl group having 2 to 30 carbon atoms, or the alkynyl group having 2 to 30 carbon atoms may have at least one type of substituent. Examples of the substituent include: Straight-chain alkyl groups having 1 to 18 carbon atoms, such as methyl, ethyl, propyl, butyl, pentyl, octyl, decyl, dodecyl, tetradecyl, hexadecyl, and octadecyl; Branched alkyl groups having 1 to 18 carbon atoms, such as isopropyl, isobutyl, sec-butyl, tert-butyl, isopentyl, neopentyl, tert-pentyl, and isohexyl; Cycloalkyl groups having 3 to 18 carbon atoms, such as cyclopropyl, cyclobutyl, cyclopentyl, and cyclohexyl; Hydroxy group; linear or branched alkoxy groups having 1 to 18 carbon atoms, such as methoxy, ethoxy, propoxy, isopropoxy, butoxy, isobutoxy, sec-butoxy, tert-butoxy, hexyloxy, decyloxy, and dodecyloxy; linear or branched alkylcarbonyl groups having 2 to 18 carbon atoms, such as acetyl, propionyl, butanoyl, 2-methylpropionyl, heptanoyl, 2-methylbutanoyl, 3-methylbutanoyl, octanoyl, decanoyl, dodecanoyl, and octadecanoyl; Arylcarbonyl groups having 7 to 11 carbon atoms, such as benzoyl and naphthoyl; linear or branched alkoxycarbonyl groups having 2 to 19 carbon atoms, such as methoxycarbonyl, ethoxycarbonyl, propoxycarbonyl, isopropoxycarbonyl, butoxycarbonyl, isobutoxycarbonyl, sec-butoxycarbonyl, tert-butoxycarbonyl, octyloxycarbonyl, tetradecyloxycarbonyl, and octadecyloxycarbonyl; Aryloxycarbonyl groups having 7 to 11 carbon atoms, such as phenoxycarbonyl and naphthoxycarbonyl; Arylthiocarbonyl groups having 7 to 11 carbon atoms, such as phenylthiocarbonyl and naphthoxythiocarbonyl; linear or branched acyloxy groups having 2 to 19 carbon atoms, such as acetoxy, ethylcarbonyloxy, propylcarbonyloxy, isopropylcarbonyloxy, butylcarbonyloxy, isobutylcarbonyloxy, sec-butylcarbonyloxy, tert-butylcarbonyloxy, octylcarbonyloxy, tetradecylcarbonyloxy, and octadecylcarbonyloxy; Phenylthio, 2-methylphenylthio, 3-methylphenylthio, 4-methylphenylthio, 2-chlorophenylthio, 3-chlorophenylthio, 4-chlorophenylthio, 2-bromophenylthio, 3-bromophenylthio, 4-bromophenylthio, 2-fluorophenylthio, 3-fluorophenylthio, 4-fluorophenylthio, 2-hydroxyphenylthio, 4-hydroxyphenylthio, 2-methoxyphenylthio, 4-methoxyphenylthio, 1-naphthylthio, 2-naphthylthio, 4-[4-(phenylthio)benzoyl]phenylthio, 4-[4-(phenylthio)phenoxy]phenylthio, 4-[4-(phenylthio)phenoxy]phenylthio, arylthio groups having 6 to 20 carbon atoms, such as arylthio)phenyl]phenylthio, 4-(phenylthio)phenylthio, 4-benzoylphenylthio, 4-benzoyl-2-chlorophenylthio, 4-benzoyl-3-chlorophenylthio, 4-benzoyl-3-methylthiophenylthio, 4-benzoyl-2-methylthiophenylthio, 4-(4-methylthiobenzoyl)phenylthio, 4-(2-methylthiobenzoyl)phenylthio, 4-(p-methylbenzoyl)phenylthio, 4-(p-ethylbenzoyl)phenylthio, 4-(p-isopropylbenzoyl)phenylthio, and 4-(p-tert-butylbenzoyl)phenylthio; linear or branched alkylthio groups having 1 to 18 carbon atoms, such as methylthio, ethylthio, propylthio, isopropylthio, butylthio, isobutylthio, sec-butylthio, tert-butylthio, pentylthio, isopentylthio, neopentylthio, tert-pentylthio, octylthio, decylthio, and dodecylthio; Aryl groups having 6 to 10 carbon atoms, such as phenyl, tolyl, dimethylphenyl, and naphthyl; heterocyclic groups having 4 to 20 carbon atoms, such as thienyl, furanyl, pyranyl, pyrrolyl, oxazolyl, thiazolyl, pyridyl, pyrimidyl, pyrazinyl, indolyl, benzofuranyl, benzothienyl, quinolyl, isoquinolyl, quinoxalinyl, quinazolinyl, carbazolyl, acridinyl, phenothiazinyl, phenazinyl, xanthenyl, thianthrenyl, phenoxazinyl, phenoxathiinyl, chromanyl, isochromanyl, dibenzothienyl, xanthonyl, thioxanthonyl, and dibenzofuranyl; aryloxy groups having 6 to 10 carbon atoms, such as phenoxy and naphthyloxy; linear or branched alkylsulfinyl groups having 1 to 18 carbon atoms, such as methylsulfinyl, ethylsulfinyl, propylsulfinyl, isopropylsulfinyl, butylsulfinyl, isobutylsulfinyl, sec-butylsulfinyl, tert-butylsulfinyl, pentylsulfinyl, isopentylsulfinyl, neopentylsulfinyl, tert-pentylsulfinyl, and octylsulfinyl; arylsulfinyl groups having 6 to 10 carbon atoms, such as phenylsulfinyl, tolylsulfinyl, and naphthylsulfinyl; linear or branched alkylsulfonyl groups having 1 to 18 carbon atoms, such as methylsulfonyl, ethylsulfonyl, propylsulfonyl, isopropylsulfonyl, butylsulfonyl, isobutylsulfonyl, sec-butylsulfonyl, tert-butylsulfonyl, pentylsulfonyl, isopentylsulfonyl, neopentylsulfonyl, tert-pentylsulfonyl, and octylsulfonyl; Arylsulfonyl groups having 6 to 10 carbon atoms, such as phenylsulfonyl, tolylsulfonyl (tosyl group), and naphthylsulfonyl; Formula (B-1-2): [ka] (Q represents a hydrogen atom or a methyl group, and k represents an integer of 1 to 5); Unsubstituted amino groups; an amino group which is mono- or di-substituted with an alkyl group having 1 to 5 carbon atoms and / or an aryl group having 6 to 10 carbon atoms; Cyano group; Nitro group; Examples of the halogen include halogens such as fluorine, chlorine, bromine and iodine.
[0050] In formula (B-1), p is [DA + R m-1 ] represents the number of repeating units of the bond, and is preferably an integer of 0 to 3.
[0051] The onium ion [A + Preferred examples of the cation include sulfonium, iodonium, and selenium, and representative examples include the following:
[0052] Examples of sulfonium ions include triphenylsulfonium, tri-p-tolylsulfonium, tri-o-tolylsulfonium, tris(4-methoxyphenyl)sulfonium, 1-naphthyldiphenylsulfonium, 2-naphthyldiphenylsulfonium, tris(4-fluorophenyl)sulfonium, tri-1-naphthylsulfonium, tri-2-naphthylsulfonium, tris(4-hydroxyphenyl)sulfonium, 4-(phenylthio)phenyldiphenylsulfonium, 4-(p-tolylthio)phenyldi-p-tolylsulfonium, 4-(4-methoxyphenylthio)phenylbis(4-methoxyphenyl)sulfonium, 4-(phenylthio)phenylbis(4-fluorophenyl)sulfonium, 4-(phenylthio)phenylbis(4-methoxyphenyl)sulfonium, 4-(phenylthio)phenyldi-p-tolylsulfonium, bis[4-(diphenylsulfonio)phenyl nyl]sulfide, bis[4-{bis[4-(2-hydroxyethoxy)phenyl]sulfonio}phenyl]sulfide, bis{4-[bis(4-fluorophenyl)sulfonio]phenyl}sulfide, bis{4-[bis(4-methylphenyl)sulfonio]phenyl}sulfide, bis{4-[bis(4-methoxyphenyl)sulfonio]phenyl}sulfide, 4-(4-benzoyl-2-chlorophenylthio)phenylbis(4-fluorophenyl)sulfonium, 4-(4-benzoyl-2-chlorophenylthio)phenyldiphenylsulfonium, 4-(4-benzoylphenylthio)phenylbis(4-fluorophenyl)sulfonium, 4-(4-benzoylphenylthio)phenyldiphenylsulfonium, 7-isopropyl-9-oxo-10-thia-9,10-dihydroanthracen-2-yldi-p-tolylsulfonium, 7-isopropyl-9-oxo-10-thia-9,10-dihydroanthracen-2-yldiphenylsulfonium, 2-[(di-p-tolyl)sulfonio]thioxanthone, 2-[(diphenyl)sulfonio]thioxanthone, 4-[4-(4-tert-butylbenzoyl)phenylthio]phenyldi-p-tolylsulfonium, 4-[4-(4-tert-butylbenzoyl)phenylthio]phenyldiphenylsulfonium, 4-[4-(benzoylphenylthio)]phenyldi-p-tolylsulfonium, 4-[4-(benzoylphenylthio)]phenyldiphenylsulfonium, 5-(4-methoxyphenyl)thiaanthrene, 5-phenylthiaanthrene, 5-tolylthianthrene, 5-(4-ethoxyphenyl)thiaanthrene, 5-(2,4,6-trimethylphenyl)thiaanthrene, and other triarylsulfonium compounds; Diarylsulfonium compounds such as diphenylphenacylsulfonium, diphenyl 4-nitrophenacylsulfonium, diphenylbenzylsulfonium, and diphenylmethylsulfonium; monoarylsulfonium compounds such as phenylmethylbenzylsulfonium, 4-hydroxyphenylmethylbenzylsulfonium, 4-methoxyphenylmethylbenzylsulfonium, 4-acetocarbonyloxyphenylmethylbenzylsulfonium, 2-naphthylmethylbenzylsulfonium, 2-naphthylmethyl(1-ethoxycarbonyl)ethylsulfonium, phenylmethylphenacylsulfonium, 4-hydroxyphenylmethylphenacylsulfonium, 4-methoxyphenylmethylphenacylsulfonium, 4-acetocarbonyloxyphenylmethylphenacylsulfonium, 2-naphthylmethylphenacylsulfonium, 2-naphthyloctadecylphenacylsulfonium, and 9-anthracenylmethylphenacylsulfonium; trialkylsulfonium such as dimethylphenacylsulfonium, phenacyltetrahydrothiophenium, dimethylbenzylsulfonium, benzyltetrahydrothiophenium, and octadecylmethylphenacylsulfonium; and the like.
[0053] Among these onium ions, one or more of sulfonium ions and iodonium ions are preferred, and sulfonium ions are more preferred. Examples of sulfonium ions include triphenylsulfonium, tri-p-tolylsulfonium, 4-(phenylthio)phenyldiphenylsulfonium, bis[4-(diphenylsulfonio)phenyl]sulfide, bis[4-{bis[4-(2-hydroxyethoxy)phenyl]sulfonio}phenyl]sulfide, bis{4-[bis(4-fluorophenyl)sulfonio]phenyl}sulfide, 4-(4-benzoyl-2-chlorophenylthio)phenylbis(4-fluorophenyl)sulfonium, 4-(4-benzoylphenylthio)phenyldiphenylsulfonium, 7-isopropyl-9-oxo-10-thia-9,10-dihydroanthracen-2-yldi-p-tolylsulfonium, 7-isopropyl-9-oxo-10-thia-9,10-dihydroanthracen-2-yldi-p-tolylsulfonium, and 7-isopropyl-9-oxo-10-thia-9 Preferred are one or more of the following: 10-dihydroanthracen-2-yldiphenylsulfonium, 2-[(di-p-tolyl)sulfonio]thioxanthone, 2-[(diphenyl)sulfonio]thioxanthone, 4-[4-(4-tert-butylbenzoyl)phenylthio]phenyldi-p-tolylsulfonium, 4-[4-(benzoylphenylthio)]phenyldiphenylsulfonium, 5-(4-methoxyphenyl)thiaanthrenenium, 5-phenylthiaanthrenenium, diphenylphenacylsulfonium, 4-hydroxyphenylmethylbenzylsulfonium, 2-naphthylmethyl(1-ethoxycarbonyl)ethylsulfonium, 4-hydroxyphenylmethylphenacylsulfonium and octadecylmethylphenacylsulfonium.
[0054] In formula (B-1), X - is a counter ion. The number of counter ions is p+1 per molecule. The counter ion is not particularly limited, but examples thereof include boron compounds, phosphorus compounds, antimony compounds, arsenic compounds, halides such as alkylsulfonic acid compounds, and methide compounds. X - For example, F - , Cl - , Br - , I -Halogen ions such as OH - ;ClO4 - ;FSO3 - , ClSO3 - , CH3SO3 - , C6H5SO3 - , CF3SO3 - Sulfonic acid ions such as HSO4 - , SO4 2- Sulfate ions such as HCO3 - , CO3 2- Carbonate ions such as H2PO4 - , HPO4 2- , PO4 3- Phosphate ions such as PF6 - , PF5OH - Fluorophosphate ions such as fluorinated alkyl fluorophosphate ions; BF4 - , B(C6F5)4 - , B(C6H4CF3)4 - Boric acid ions such as AlCl4 - ;BiF6 - Other examples include SbF6 - , SbF5OH - Fluoroantimonate ions such as AsF6 - , AsF5OH - and the like fluoroarsenate ions.
[0055] Examples of the fluorinated alkyl fluorophosphate ion include a fluorinated alkyl fluorophosphate ion represented by the formula (B-1-3) and the like. [(Rf) b PF 6-b ] - (B-1-3)
[0056] In formula (B-1-3), Rf represents an alkyl group substituted with a fluorine atom. The number b of Rf is 1 to 5, and is preferably an integer. The b number of Rf may be the same or different. The number b of Rf is more preferably 2 to 4, and most preferably 2 to 3.
[0057] In the fluorinated alkyl fluorophosphate ion represented by formula (B-1-3), Rf represents an alkyl group substituted with a fluorine atom, preferably having 1 to 8 carbon atoms, more preferably 1 to 4 carbon atoms. Examples of the alkyl group include linear alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, and octyl; branched alkyl groups such as isopropyl, isobutyl, sec-butyl, and tert-butyl; and cycloalkyl groups such as cyclopropyl, cyclobutyl, cyclopentyl, and cyclohexyl. Specific examples of Rf include CF3, CF3CF2, (CF3)2CF, CF3CF2CF2, CF3CF2CF2CF2, (CF3)2CFCF2, CF3CF2(CF3)CF, and (CF3)3C.
[0058] A specific example of a preferred fluorinated alkyl fluorophosphate anion is [(CF3CF2)2PF4] - , [(CF3CF2)3PF3] - , [((CF3)2CF)2PF4] - , [((CF3)2CF)3PF3] - , [(CF3CF2CF2)2PF4] - , [(CF3CF2CF2)3PF3] - , [((CF3)2CFCF2)2PF4] - , [((CF3)2CFCF2)3PF3] - , [(CF3CF2CF2CF2)2PF4] - and [(CF3CF2CF2CF2)3PF3] - etc.
[0059] The photocationic polymerization initiator may be dissolved in advance in a solvent to facilitate mixing with the polymerizable compound. Examples of the solvent include carbonates such as propylene carbonate, ethylene carbonate, 1,2-butylene carbonate, dimethyl carbonate, and diethyl carbonate.
[0060] The photocationic polymerization initiator is preferably a compound represented by formula (1). Examples of the compound represented by formula (1) include triarylsulfonium tris(pentafluorophenyl)borate, triarylsulfonium hexafluoroantimonate, and triarylsulfonium hexafluorophosphate. [ka]
[0061] In formula (1), R 1 represents a hydrogen atom, an optionally substituted alkyl group or an optionally substituted aryl group; X - indicates a monovalent anion. 1 may be the same or different from each other.
[0062] R 1 Examples of the alkyl group in R include the same alkyl groups having 1 to 30 carbon atoms as those in R. 1 Examples of the aryl group in R include the same aryl groups having 6 to 30 carbon atoms as those in R above.
[0063] X - Examples of the above are the same as those mentioned above.
[0064] R 1 is preferably an optionally substituted alkyl group or an optionally substituted aryl group, and more preferably an optionally substituted aryl group.
[0065] The photoradical polymerization initiator is not particularly limited, but may be, Benzophenone and its derivatives; Benzil and its derivatives; Anthraquinone and its derivatives; Benzoin-type photopolymerization initiators such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isobutyl ether, and benzil dimethyl ketal; Acetophenone-type photopolymerization initiators such as diethoxyacetophenone and 4-tert-butyltrichloroacetophenone; 2-Dimethylaminoethyl benzoate; p-Dimethylaminoethyl benzoate; Diphenyl disulfide; Thioxanthone and its derivatives; camphorquinone-type photopolymerization initiators such as camphorquinone, 7,7-dimethyl-2,3-dioxobicyclo[2.2.1]heptane-1-carboxylic acid, 7,7-dimethyl-2,3-dioxobicyclo[2.2.1]heptane-1-carboxy-2-bromoethyl ester, 7,7-dimethyl-2,3-dioxobicyclo[2.2.1]heptane-1-carboxy-2-methyl ester, and 7,7-dimethyl-2,3-dioxobicyclo[2.2.1]heptane-1-carboxylic acid chloride; α-aminoalkylphenone type photopolymerization initiators such as 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1; Acylphosphine oxide type photopolymerization initiators such as benzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, benzoyldiethoxyphosphine oxide, 2,4,6-trimethylbenzoyldimethoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyldiethoxyphenylphosphine oxide, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide; Phenyl-glyoxylic acid-methyl ester; Oxy-phenyl-acetic acid 2-[2-oxo-2-phenyl-acetoxy-ethoxy]-ethyl ester; Oxy-phenyl-acetic acid 2-[2-hydroxy-ethoxy]-ethyl ester; and the like.
[0066] The content of the photopolymerization initiator is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, even more preferably 0.3 parts by mass or more, and even more preferably 0.5 parts by mass or more, relative to 100 parts by mass of the polymerizable compound. This further improves the curability. In addition, the content of the polymerization initiator is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, relative to 100 parts by mass of the polymerizable compound. This allows the formation of a sealing material with excellent reliability during long-term storage. That is, the content of the photopolymerization initiator may be, for example, 0.01 to 5 parts by mass, 0.01 to 3 parts by mass, 0.1 to 5 parts by mass, 0.1 to 3 parts by mass, 0.3 to 5 parts by mass, 0.3 to 3 parts by mass, 0.5 to 5 parts by mass, or 0.5 to 3 parts by mass, relative to 100 parts by mass of the polymerizable compound.
[0067] As the inorganic fine particles, crystalline silica, amorphous silica, alumina, magnesia, zirconia, talc, mica, clay, kaolin, rutile titanium oxide, anatase titanium oxide, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, magnesium sulfate, barium sulfate, aluminum hydroxide, magnesium hydroxide, etc. can be used. As the inorganic fine particles, spherical inorganic fine particles such as spherical silica, spherical alumina, spherical magnesia, and spherical zirconia can be suitably used. When the inorganic fine particles are spherical, the irradiated light is diffusely reflected at the interface between the polymerizable compound in the composition and the inorganic fine particles, and the irradiated light easily reaches the depth of the composition, which tends to make it easier to satisfy the above-mentioned suitable curing depth.
[0068] The average circularity (roundness) of the inorganic fine particles is preferably 0.7 or more, more preferably 0.8 or more, and even more preferably 0.85 or more. This tends to make the above-mentioned diffuse reflection effect more pronounced. The average circularity of the inorganic fine particles may be 1.0 or less.
[0069] In this specification, the average circularity of inorganic fine particles is a number-average value calculated by measuring the projected area and perimeter of primary particles of inorganic fine particles observed by microscope and using the following formula: Average circularity = 4 x π x (projected area) / (perimeter)2
[0070] The inorganic fine particles preferably have a refractive index close to that of the polymerizable compound. The absolute value of the difference between the refractive index n1 of the polymer of the polymerizable compound and the refractive index n2 of the inorganic fine particles (|n1-n2|) may be, for example, 0.6 or less, preferably 0.5 or less, more preferably 0.4 or less, even more preferably 0.3 or less, and even more preferably 0.25 or less, and may be 0.2 or less, 0.15 or less, or 0.1 or less. When the inorganic fine particles have a refractive index close to that of the polymerizable compound, the reflection of the irradiated light is less likely to occur at the interface between the inorganic fine particles and the polymerizable compound, and the irradiated light is more likely to reach the depth of the composition, which tends to make it easier to meet the above-mentioned suitable curing depth.
[0071] In this specification, the refractive index n2 of inorganic fine particles is a value calculated by measuring the refractive index n' of a mixture prepared by dispersing inorganic fine particles in a predetermined volume fraction v in a liquid having a known refractive index n as a standard sample using a refractometer, and then calculating the refractive index n' using the following formula. n2=(n'-n) / v+n
[0072] When the composition of the present embodiment contains multiple types of inorganic microparticles, it is preferable that |n1-n2| of the inorganic microparticles contained most abundantly (for example, 50 vol.% or more, 60 vol.% or more, 70 vol.% or more, 80 vol.% or more, or 90 vol.% or more based on the total amount of inorganic microparticles) is in the above range, and it is more preferable that |n1-n2| of all inorganic microparticles is in the above range.
[0073] The refractive index n2 of the inorganic fine particles is not particularly limited, and is, for example, 1.3 or more, preferably 1.4 or more. The refractive index n2 of the inorganic fine particles is, for example, 2.5 or less, preferably 2.3 or less, more preferably 2.0 or less, even more preferably 1.8 or less, and even more preferably 1.6 or less, and may be 1.5 or less. The refractive index n2 of the inorganic fine particles is measured, for example, by an Abbe refractometer. That is, the refractive index n2 of the inorganic fine particles may be, for example, 1.3 to 2.5, 1.3 to 2.3, 1.3 to 2.0, 1.3 to 1.8, 1.3 to 1.6, 1.3 to 1.5, 1.4 to 2.5, 1.4 to 2.3, 1.4 to 2.0, 1.4 to 1.8, 1.4 to 1.6, or 1.4 to 1.5.
[0074] The average particle size of the inorganic fine particles may be, for example, 0.1 μm or more, preferably 0.5 μm or more, more preferably 1 μm or more. When the average particle size of the inorganic fine particles is large, the effect of inhibiting moisture permeation in the cured body is easily obtained. In addition, the average particle size of the inorganic fine particles may be, for example, 50 μm or less, preferably 30 μm or less, more preferably 10 μm or less. When the average particle size of the inorganic fine particles is small, the inorganic fine particles are less likely to separate in the composition, a more uniform cured body is more easily obtained, and long-term reliability tends to be improved. That is, the average particle size of the inorganic fine particles may be, for example, 0.1 to 50 μm, 0.1 to 30 μm, 0.1 to 10 μm, 0.5 to 50 μm, 0.5 to 30 μm, 0.5 to 10 μm, 1 to 50 μm, 1 to 30 μm, or 1 to 10 μm.
[0075] In this specification, the average particle size of inorganic fine particles refers to a value measured by a laser diffraction / scattering method using a Microtrac particle size distribution device.
[0076] The content of inorganic fine particles is 30% by volume or more, preferably 32% by volume or more, more preferably 35% by volume or more, and may be 40% by volume or more or 45% by volume or more. By increasing the content of inorganic fine particles while maintaining a sufficient curing depth, the moisture permeability of the cured body tends to be further reduced. The upper limit of the content of inorganic fine particles is not particularly limited as long as the above-mentioned curing depth can be maintained. The content of inorganic fine particles may be, for example, 80% by volume or less, preferably 70% by volume or less, more preferably 65% by volume or less, and may be 60% by volume or less, 55% by volume or less, or 50% by volume or less. By reducing the content of inorganic fine particles, the above-mentioned curing depth tends to be more easily satisfied. That is, the content of the inorganic fine particles is, for example, 30 to 80 volume%, 30 to 70 volume%, 30 to 65 volume%, 30 to 60 volume%, 30 to 55 volume%, 30 to 50 volume%, 32 to 80 volume%, 32 to 70 volume%, 32 to 65 volume%, 32 to 60 volume%, 32 to 55 volume%, 32 to 50 volume%, 35 to 80 volume%, 35 to 70 volume%, 35 It may be 40 to 80 volume%, 40 to 70 volume%, 40 to 65 volume%, 40 to 60 volume%, 40 to 55 volume%, 40 to 50 volume%, 45 to 80 volume%, 45 to 70 volume%, 45 to 65 volume%, 45 to 60 volume%, 45 to 55 volume%, or 45 to 50 volume%.
[0077] The composition of the present embodiment may further contain a photosensitizer. The photosensitizer refers to a compound that can absorb energy rays and efficiently generate reactive species (e.g., cations generated from a photocationic polymerization initiator, and radicals generated from a photoradical polymerization initiator) from a polymerization initiator.
[0078] The photosensitizer is not particularly limited, and examples thereof include benzophenone derivatives, phenothiazine derivatives, phenylketone derivatives, naphthalene derivatives, anthracene derivatives, phenanthrene derivatives, naphthacene derivatives, chrysene derivatives, perylene derivatives, pentacene derivatives, acridine derivatives, benzothiazole derivatives, benzoin derivatives, fluorene derivatives, naphthoquinone derivatives, anthraquinone derivatives, xanthene derivatives, xanthone derivatives, thioxanthene derivatives, thioxanthone derivatives, coumarin derivatives, ketocoumarin derivatives, cyanine derivatives, azine derivatives, thiazine derivatives, oxazine derivatives, indoline derivatives, azulene derivatives, triarylmethane derivatives, phthalocyanine derivatives, spiropyran derivatives, spirooxazine derivatives, thiospiropyran derivatives, and organic ruthenium complexes. Among these, phenylketone derivatives such as 2-hydroxy-2-methyl-1-phenyl-propan-1-one and anthracene derivatives such as 9,10-dibutoxyanthracene are preferred, and anthracene derivatives are more preferred. Among the anthracene derivatives, 9,10-dibutoxyanthracene is preferred. The photosensitizer may be used alone or in combination of two or more kinds.
[0079] A suitable photosensitizer is, for example, a photosensitizer represented by the following formula (2): A suitable photosensitizer represented by the following formula (2) is, for example, dibutoxyanthracene. [ka]
[0080] In formula (2), R 2 represents an alkyl group which may have a substituent.
[0081] R 2 The number of carbon atoms in the alkyl group may be, for example, 1 to 10, preferably 2 to 8, and more preferably 2 to 6. That is, R 2 The alkyl group may have, for example, 1 to 10, 1 to 8, 1 to 6, 2 to 10, 2 to 8, or 2 to 6 carbon atoms.
[0082] When the composition of the present embodiment contains a photosensitizer, the content of the photosensitizer may be, for example, 0.01 parts by mass or more, or 0.05 parts by mass or more, relative to 100 parts by mass of the polymerizable compound. In addition, from the viewpoint of storage stability, the content of the photosensitizer may be, for example, 5 parts by mass or less, and preferably 3 parts by mass or less, relative to 100 parts by mass of the polymerizable compound. That is, the content of the photosensitizer may be, for example, 0.01 to 5 parts by mass, 0.01 to 3 parts by mass, 0.05 to 5 parts by mass, or 0.05 to 3 parts by mass, relative to 100 parts by mass of the polymerizable compound.
[0083] The composition of the present embodiment may further contain other components other than those described above. As the other components, for example, known additives used in the field of sealants can be used without particular limitation. As the other components, for example, silane coupling agents, antioxidants, resin particles, metal deactivators, fillers, stabilizers, neutralizers, lubricants, antibacterial agents, etc. can be mentioned.
[0084] The content of other components is not particularly limited and may be, for example, 10 mass % or less, 5 mass % or less, or 1 mass % or less based on the total amount of the composition.
[0085] The method for producing the composition of the present embodiment is not particularly limited, and each of the above-mentioned components may be mixed by a mixing method having the stirring ability to sufficiently mix each of the above-mentioned components. Examples of the mixing method include a method of stirring by applying a rotational force to a stirrer such as a stirring blade, a screw, or a magnetic stirrer, a method of stirring by rotating a container such as a tumbler mixer or a planetary stirrer, a method of stirring by using a shear force from a stirring ball such as a bead mill, a method of stirring by using a compression force such as a roll mill, a method of stirring by using a vibration force such as a shaker, a method of stirring by using the turbulence of the mixture itself such as a vortex mixer, and a method of stirring by using ultrasonic waves such as an ultrasonic stirrer, and other methods using known dispersing machines. Among these, from the viewpoint of being able to mix each of the above-mentioned components sufficiently and safely and minimizing impurities such as stirrers, a method of stirring by rotating a container such as a planetary stirrer is preferred. Examples of the method of stirring by rotating a container include a method using a vacuum rotation revolution mixer.
[0086] By curing the composition of the present embodiment, a cured product containing a polymer of the polymerizable compound and inorganic fine particles can be obtained. The cured product has low moisture permeability and can be suitably used as a sealant (particularly, a sealant for an organic electroluminescence display device, and a dam in a dam-fill sealing structure).
[0087] The composition of the present embodiment can be cured, for example, by irradiation with energy rays. From the viewpoints of reaction efficiency and safety, ultraviolet light and visible light are preferably used as the energy rays. The light source used to cure the composition of the present embodiment is not particularly limited, and examples thereof include halogen lamps, metal halide lamps, high-power metal halide lamps (containing indium, etc.), low-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, xenon lamps, xenon excimer lamps, xenon flash lamps, and light-emitting diodes (hereinafter referred to as LEDs). Natural light (sunlight) can also be a reaction initiation light source. Among these light sources, LED light sources are preferred because they can selectively irradiate the desired wavelength.
[0088] The wavelength of the light source is not particularly limited, and the light source is appropriately selected depending on the reaction wavelength of the polymerization initiator, etc. The wavelength can be 400 nm or less from the viewpoint of reactivity efficiency, preferably 395 nm or less, more preferably 385 nm or less, and even more preferably 365 nm or less. Also, from the viewpoint of curing depth efficiency, the wavelength can be 300 nm or more, preferably 320 nm or more, more preferably 340 nm or more, and even more preferably 365 nm or more. That is, the wavelength of the light source may be, for example, 300 to 400 nm, 300 to 395 nm, 300 to 385 nm, 300 to 365 nm, 320 to 400 nm, 320 to 395 nm, 320 to 385 nm, 320 to 365 nm, 340 to 400 nm, 340 to 395 nm, 340 to 385 nm, 340 to 365 nm, 365 to 400 nm, 365 to 395 nm, or 365 to 385 nm.
[0089] The method of irradiation with the above light source may be direct irradiation or focused irradiation using a reflecting mirror, fiber, etc. Furthermore, irradiation using a low wavelength cut filter, a heat ray cut filter, a cold mirror, etc. may also be used.
[0090] The irradiation dose of the light source may be appropriately selected depending on the thickness of the composition. For example, the irradiation dose for a composition having a thickness of 100 μm is 600 mJ / cm 2 More preferably, 1000 mJ / cm 2 It is more preferable that the irradiation amount is equal to or more than 100 μm. For a composition having a thickness of less than 100 μm, the irradiation amount may be appropriately adjusted according to the thickness (for example, in proportion to the thickness).
[0091] When curing the composition of the present embodiment, a post-heating treatment may be performed after the light irradiation to accelerate the curing. The post-heating temperature is preferably 150°C or less, more preferably 100°C or less, and may be 90°C or less or 80°C or less, from the viewpoint of avoiding an influence on the organic EL display element. The post-heating temperature is preferably 40°C or more, and may be 50°C or more, 60°C or more, 70°C or more, or 80°C or more. That is, the post-heating temperature may be, for example, 40 to 150°C, 40 to 100°C, 40 to 90°C, 40 to 80°C, 50 to 150°C, 50 to 100°C, 50 to 90°C, 50 to 80°C, 60 to 150°C, 60 to 100°C, 60 to 90°C, 60 to 80°C, 70 to 150°C, 70 to 100°C, 70 to 90°C, or 70 to 80°C. From the viewpoint of avoiding influence on the organic EL display element, the post-treatment time is preferably 120 minutes or less, more preferably 60 minutes or less, and even more preferably 30 minutes or less. The post-treatment time may be 5 minutes or more, or may be 10 minutes or more, preferably 20 minutes or more, and more preferably 30 minutes or more. That is, the post-treatment time may be, for example, 5 to 120 minutes, 5 to 60 minutes, 5 to 30 minutes, 10 to 120 minutes, 10 to 60 minutes, 10 to 30 minutes, 20 to 120 minutes, 20 to 60 minutes, 20 to 30 minutes, 30 to 120 minutes, or 30 to 60 minutes.
[0092] The composition of the present embodiment can also be used as an adhesive. For example, the composition of the present embodiment can be suitably used for bonding packages of organic EL display elements and the like.
[0093] A method for bonding two members using the composition of the present embodiment includes, for example, a method including a step of applying the composition to the entire surface or a part of the first member, a step of irradiating the composition applied to the first member with light, and a step of bonding the first member and the second member via the composition until the composition irradiated with light is cured. According to such a method, the second member can be bonded to the first member without being exposed to light and heat. Therefore, the above method can be suitably used for bonding a back panel and an organic EL display element.
[0094] A method for producing an organic EL display device using the composition of the present embodiment includes, for example, a production method including the steps of applying the composition onto a back panel, irradiating the composition applied onto the back panel with light, and bonding the back panel and a substrate on which an organic EL display element is formed via the composition while blocking the light. According to such a method, the organic EL display element can be sealed without being exposed to light and heat.
[0095] In addition, a method for producing an organic EL display device using the composition of the present embodiment may include, for example, a production method including a step of applying the composition to one substrate, a step of bonding the one substrate and the other substrate via the composition, and a step of irradiating the composition between the substrates with light to cure the composition.
[0096] The composition of this embodiment has a wavelength of 365 nm and an irradiation dose of 600 mJ / cm 2The curing depth is 100 μm or more when the composition is irradiated with light and left at 80° C. for 30 minutes. The curing depth is preferably 120 μm or more, more preferably 140 μm or more, even more preferably 160 μm or more, and even more preferably 180 μm or more, and may be 200 μm or more, 250 μm or more, 300 μm or more, 350 μm or more, 400 μm or more, 450 μm or more, or 500 μm or more. When the curing depth is large, the decrease in moisture resistance and reliability caused by the remaining unreacted monomer is suppressed, and there is a tendency for better moisture resistance and long-term reliability to be realized. The upper limit of the curing depth is not particularly limited. The curing depth may be, for example, 1000 μm or less, preferably 800 μm or less, and more preferably 700 μm or less. That is, the above-mentioned hardening depth is, for example, 100 to 1000 μm, 100 to 800 μm, 100 to 700 μm, 120 to 1000 μm, 120 to 800 μm, 120 to 700 μm, 140 to 1000 μm, 140 to 800 μm, 140 to 700 μm, 160 to 1000 μm, 160 to 800 μm, 160 to 700 μm, 180 to 1000 μm, 180 to 800 μm, 180 to 700 μm, 200 to 1000 μm, 200 to 800 μm, 200 to 7 00 μm, 250 to 1000 μm, 250 to 800 μm, 250 to 700 μm, 300 to 1000 μm, 300 to 800 μm, 300 to 700 μm, 350 to 1000 μm, 350 to 800 μm, 350 to 700 μm, 400 to 1000 μm, 400 to 800 μm, 400 to 700 μm, 450 to 1000 μm, 450 to 800 μm, 450 to 700 μm, 500 to 1000 μm, 500 to 800 μm, or 500 to 700 μm.
[0097] In the composition of the present embodiment, the type and content of each component may be appropriately adjusted so that the cure depth falls within the above range.
[0098] The specific gravity of the cured product of the composition of this embodiment (hereinafter also simply referred to as the cured product of this embodiment) is, for example, 1.3 or more, preferably 1.5 or more, and more preferably 1.7 or more. The specific gravity of the cured product of this embodiment may be, for example, 5.0 or less, and preferably 3.0 or less. That is, the specific gravity of the cured product of this embodiment may be, for example, 1.3 to 5.0, 1.3 to 3.0, 1.5 to 5.0, 1.5 to 3.0, 1.7 to 5.0, or 1.7 to 3.0. The specific gravity of the cured product is a value measured in accordance with JIS K7112 B method using water at 23°C as an immersion liquid.
[0099] In the composition of the present embodiment, the type and content of each component may be appropriately adjusted so that the specific gravity of the cured product falls within the above range.
[0100] In the cured product of the present embodiment, the glass transition temperature of the polymer of the polymerizable compound may be, for example, 80° C. or higher, preferably 85° C. or higher, more preferably 90° C. or higher, and even more preferably 100° C. or higher. The glass transition temperature of the polymer of the polymerizable compound may be, for example, 250° C. or lower.
[0101] In this specification, the glass transition temperature (Tg) of a polymer refers to a value determined from a dynamic viscoelasticity spectrum. In the dynamic viscoelasticity spectrum, when a polymer that is solid at a certain temperature is subjected to stress and strain at that temperature and then heated at a constant heating rate, the glass transition temperature can be determined as the temperature at which the storage modulus decreases and the loss tangent (hereinafter abbreviated as tan δ) reaches a peak top.
[0102] In the composition of the present embodiment, the type and content of each component may be appropriately adjusted so that the glass transition temperature of the polymer falls within the above range.
[0103] The viscosity of the composition of this embodiment is, for example, 0.1 Pa·s or more, preferably 1 Pa·s or more, more preferably 10 Pa·s or more, and even more preferably 100 Pa·s or more. When the viscosity of the composition is high, the composition is less likely to flow during curing, and a cured body with stable dimensions is more likely to be obtained. The viscosity of the composition of this embodiment is, for example, 10000 Pa·s or less, preferably 1000 Pa·s or less. When the viscosity of the composition is low, the composition is easy to process and handle. That is, the viscosity of the composition of this embodiment may be 0.1 to 10000 Pa·s, 0.1 to 1000 Pa·s, 1 to 10000 Pa·s, 1 to 1000 Pa·s, 10 to 10000 Pa·s, 100 to 10000 Pa·s, or 100 to 1000 Pa·s. The viscosity is measured at 23° C. using a cone-plate viscometer in accordance with JIS K5600 2-3.
[0104] The cured product of the present embodiment has a moisture permeability of 150 g / (m) per 100 μm thickness, measured under conditions of a temperature of 85° C. and a relative humidity of 85% in accordance with JIS Z0208. 2 24 hours) or less, and 130g / (m 2 24 hours) or less, and 100g / (m 2 24 hours) or less, and 80 g / (m 2 24 hours) or less, and 60 g / (m 2 24 hours) or less, 50g / (m 2 The moisture permeability may be less than or equal to 100 μm in thickness (g / m 2 ). The moisture permeability is measured by exposing the film to an environment of 85° C. and 85% RH for 24 hours in accordance with JIS Z 0208:1976. 2 The moisture permeability can be, for example, 0.01 (g / m 2 24 hours) or more, and 2 24 hours) or more, and 2 24 hours) or more, and 5 (g / m 2 That is, the moisture permeability may be, for example, 0.01 to 150 g / (m2 ·24 hours), 0.01~130g / (m 2 ·24 hours), 0.01~100g / (m 2 ·24 hours), 0.01~80g / (m 2 ·24 hours), 0.01~60g / (m 2 ·24 hours), 0.01~50g / (m 2 ·24 hours), 0.1~150g / (m 2 ·24 hours), 0.1~130g / (m 2 ·24 hours), 0.1~100g / (m 2 ·24 hours), 0.1~80g / (m 2 ·24 hours), 0.1~60g / (m 2 ·24 hours), 0.1~50g / (m 2 ·24 hours), 1~150g / (m 2 ·24 hours), 1~130g / (m 2 ·24 hours), 1~100g / (m 2 ·24 hours), 1~80g / (m 2 ·24 hours), 1~60g / (m 2 ·24 hours), 1~50g / (m 2 ·24 hours), 5~150g / (m 2 ·24 hours), 5~130g / (m 2 ·24 hours), 5~100g / (m 2 ·24 hours), 5~80g / (m 2 ·24 hours), 5~60g / (m 2 24 hours) or 5~50g / (m 2 -24 hours).
[0105] In the composition of the present embodiment, the type and content of each component may be appropriately adjusted so that the moisture permeability of the cured product falls within the above range.
[0106] The cured body of the present embodiment may have a water absorption rate of, for example, 15% or less at a temperature of 85° C. and a relative humidity of 85% for 24 hours, preferably 10% or less, more preferably 5% or less, and even more preferably 3% or less, and may be 2% or less, 1.5% or less, or 1% or less. This tends to suppress a decrease in moisture resistance and reliability caused by residual moisture in the cured body, and to achieve better moisture resistance and long-term reliability.
[0107] In the composition of the present embodiment, the type and content of each component may be appropriately adjusted so that the water absorption rate of the cured product falls within the above range.
[0108] Although the preferred embodiments of the present invention have been described above, the present invention is not limited to the above-described embodiments.
[0109] For example, the present invention may relate to a method for producing an organic electroluminescent display device having a dam-fill sealing structure, comprising the steps of applying and curing the above-mentioned composition to form a dam.
[0110] The present invention may also relate to an organic electroluminescence display device having a dam-fill sealing structure consisting of a dam and a fill agent, in which case the dam may contain a cured product of the above-mentioned composition.
[0111] The dam-fill sealing structure may be a known dam-fill sealing structure, the filler may be a known filler, and the configuration of the organic EL display device other than the dam-fill sealing structure may be the same as that of a known organic EL display device.
[0112] The organic EL display element may be an organic EL television. According to the present invention, it is possible to provide a sealant capable of realizing sufficient moisture resistance and long-term reliability in organic EL televisions, which are becoming significantly larger. EXAMPLES
[0113] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Unless otherwise specified, the examples were tested at 23° C. and a relative humidity of 50% by mass.
[0114] The following compounds were used in the examples and comparative examples.
[0115] (A) Polymerizable compound (A-1) Glycidyl methacrylate (Kyoeisha Chemical Co., Ltd. "Light Ester G", specific gravity: 1.1, refractive index: 1.45, molecular weight: 142) (A-2) Neopentyl glycol diglycidyl ether ("ED523T" manufactured by Adeka Corporation, specific gravity: 1.1, refractive index: 1.48, molecular weight: 216) (A-3) Tetrabromobisphenol A diglycidyl ether (DIC Corporation "Epicron 152", specific gravity: 1.7, refractive index: 1.60, molecular weight: 972) (A-4) 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate (Daicel Chemical Industries, Ltd. "Celloxide 2021", specific gravity: 1.2, refractive index: 1.52, molecular weight: 252) (A-5) 1,10-Decanediol dimethacrylate ("NK Ester DOD-N" manufactured by Shin-Nakamura Chemical Co., Ltd., specific gravity: 1.0, refractive index: 1.46)
[0116] (B) Polymerization initiator (B-1) Triarylsulfonium tris(pentafluorophenyl)borate ("CPI-310B" manufactured by San-Apro Co., Ltd.) (B-2) Benzyl dimethyl ketal (BASF "Irgacure TPO")
[0117] (C) Inorganic fine particles (C-1) Spherical silica ("FB-5SDC" manufactured by Denka Co., Ltd., average particle size: 4 μm, circularity: 0.9, refractive index: 1.44, specific gravity: 2.1) (C-2) Spherical alumina (Denka "DAW-05", average particle size: 5 μm, circularity: 0.95, refractive index: 1.77, specific gravity: 3.9) (C-3) Plate-shaped talc (Matsumura Sangyo "High Filler #17", average particle size: 12 μm, circularity: 0.5, refractive index: 1.57, specific gravity: 2.7) (C-4) Rutile titanium dioxide (Ishihara Sangyo "CR-EL", average particle size: 0.25 μm, circularity: 0.7, refractive index: 2.13, specific gravity: 4.2)
[0118] (D) Photosensitizer (D-1) Dibutoxyanthracene (Kawasaki Chemical Industries, Ltd. "Anthracure UVS-1331")
[0119] (Examples 1 to 7 and Comparative Examples 1 to 4) The raw materials shown in Tables 1 to 3 were weighed out in the proportions shown in Tables 1 to 3, and mixed at 600 rpm for 5 minutes in a vacuum planetary centrifugal mixer (EME "UFO-S3") to prepare compositions of the examples and comparative examples. The blending proportions are shown in parts by mass. The content of inorganic fine particles was calculated as a volume percentage from the specific gravity and is shown in % by volume.
[0120] The following values were determined for each composition of the Examples and Comparative Examples. The results are shown in Tables 1 to 3.
[0121] <Refractive index of polymer of polymerizable compound> The polymerizable compound and the polymerization initiator were weighed out in the ratios shown in Tables 1 to 3, and mixed at 2000 rpm for 5 minutes using a planetary centrifugal mixer (Thinky "AR-250") to obtain a mixture. The mixture was then applied to a polyethylene terephthalate film to a thickness of 100 μm, and irradiated with an LED light source with a wavelength of 365 nm at a dose of 600 mJ / cm. 2 The sample was irradiated with ultraviolet light of 1000 nm and left to stand at 80° C. for 30 minutes. The polyethylene terephthalate film was then peeled off to obtain a measurement sample. The refractive index of the measurement sample was measured using an Abbe refractometer (ATAGO "DR-M2").
[0122] <Curing depth> The composition was filled into a urethane tube with an inner diameter of 4 mm and a depth of 8 mm, the sides and bottom of which were covered with aluminum foil, and the tube was placed on a hot plate at 80°C and irradiated from the top of the tube with an LED light source with a wavelength of 365 nm at a dose of 600 mJ / cm.2 After irradiation, the tube was left to stand at 80°C for 30 minutes, and then the uncured part at the bottom of the tube was wiped off with gauze soaked in ethanol, and the thickness of the remaining cured part was measured with a micrometer (manufactured by Mitutoyo Corporation).
[0123] <Total light transmittance, total light reflectance> The composition was applied to a glass sheet to a thickness of 100 μm, and then another sheet of glass was placed on top of the composition to form a three-layer structure of glass / composition / glass. After base correction was performed using two sheets of uncoated glass with a haze meter (Nippon Denshoku "NDH-8000"), the total light transmittance and total light reflectance of the above three-layer structure sample were measured.
[0124] <Preparation of hardened body> The composition was applied to a polyethylene terephthalate film to a thickness of 100 μm. Then, the composition was irradiated with an LED light source having a wavelength of 365 nm at a dose of 600 mJ / cm. 2 After irradiation with ultraviolet light of 1000 nm, the mixture was allowed to stand for 30 minutes at 80° C. The polyethylene terephthalate film was then peeled off to obtain a cured product.
[0125] <Refractive index difference> The refractive index was calculated from the following formula using the refractive index n1 of the polymer of the polymerizable compound obtained by the above method and the refractive index n2 of the inorganic fine particles. However, when the composition contains multiple inorganic fine particles, |n1-n2| was calculated for each inorganic fine particle, and the maximum value was listed in the table. Refractive index difference = |n1-n2| In Example 6, the maximum value of |n1-n2| is 0.57, but the majority of the inorganic fine particles are inorganic fine particles ((C-1) spherical silica) with |n1-n2| of 0.5 or less.
[0126] <Specific gravity of hardened body> The specific gravity of the cured body was measured using a specific gravity measurement kit manufactured by Mettler Toledo Co., Ltd. The measurement atmosphere was 23°C.
[0127] <Moisture permeability> The moisture permeability of the cured body was measured in accordance with the moisture permeability cup method of JIS Z 0208, except that the test conditions were 85° C., 85% RH, and 24 hours.
[0128] <Moisture absorption rate (water absorption rate)> The hardened material was left to stand in an atmosphere of 23°C and 50% RH for 24 hours, then humidified in an atmosphere of 85°C and 85% RH for 24 hours, and then cooled again at 23°C and 50% RH for 1 hour. The moisture content (%) was measured using the Karl Fischer method, and this value was taken as the moisture absorption rate.
[0129] Next, for each composition of the examples and comparative examples, a side sealing substrate was produced by the following method, and the cured state of the sealing material was evaluated and a reliability test was performed. The results are shown in Tables 1 to 3.
[0130] <Preparation of side sealing substrate> On a non-alkali glass of 30 mm square, 4 mL of the composition was applied to draw a square of about 17 mm square using a tabletop applicator (Musashi Engineering, SHOTmini) with a nozzle diameter of 0.2 mm to prepare a first glass substrate. Next, a glass substrate (Q-Lights) on which metallic calcium was evaporated to a thickness of 0.2 μm over an area of 13 mm square was prepared as a second glass substrate, and the first glass substrate and the second glass substrate were bonded together. At this time, the positions of the first glass substrate and the second glass substrate were adjusted so that the composition on the first glass substrate surrounded the metallic calcium on the second glass substrate. Then, a 365 nm wavelength, 600 mJ / cm irradiance was applied from the first glass substrate side. 2 After being irradiated with ultraviolet light of 1000 nm, the substrate was pressed under a load of 0.1 MPa at 40° C. in a vacuum press machine. The substrate was then heated in an oven at 80° C. for 30 minutes to obtain a side-sealed substrate whose side surfaces were sealed with a sealant made of a cured product of the composition.
[0131] <Evaluation of the cured state> The side sealing substrate was visually inspected, and the case where there was no uncured part in the sealing material was rated as A, and the case where there was an uncured part in the sealing material was rated as C.
[0132] <Reliability test> The side sealing substrate was left to stand in an atmosphere of 85° C. and 85% RH, and the time until the black metallic calcium layer completely turned white due to reaction with water was measured.
[0133] [Table 1]
[0134] [Table 2]
[0135] [Table 3]
Claims
1. A polymerizable compound comprising at least one selected from the group consisting of an alicyclic epoxy compound and an acyclic epoxy compound; At least one type of inorganic fine particles selected from the group consisting of spherical silica, spherical alumina, spherical magnesia, and spherical zirconia; A photopolymerization initiator; Contains The content of the inorganic fine particles is 30% by volume or more, The mixture was packed into a urethane tube with an inner diameter of 4 mm and a depth of 8 mm, the sides and bottom of which were covered with aluminum foil, and the tube was placed on a hot plate at 80°C and irradiated from the top of the tube with an LED light source with a wavelength of 365 nm at a dose of 600 mJ / cm. 2 and leaving it at 80°C for 30 minutes, the curing depth is 100 µm or more. composition.
2. The inorganic fine particles have a refractive index n 1 The absolute value of the difference between 1 -n 2 |) is 0.5 or less, 2 The composition according to claim 1 , which is an inorganic particulate having the formula:
3. The refractive index n of the inorganic fine particles 2 The composition according to claim 1 or 2, wherein the σ is 1.4 or more.
4. The composition according to any one of claims 1 to 3, wherein the inorganic fine particles have an average circularity of 0.7 or more and 1.0 or less.
5. The composition according to any one of claims 1 to 4, wherein the inorganic fine particles comprise at least one selected from the group consisting of spherical silica and spherical alumina.
6. Total light transmittance T per 100 μm thickness 0 (%) and total light reflectance R 0 (%) and the sum (T 0 +R 0 6. The composition according to claim 1, wherein the content of the hydroxypropyl ether in the hydroxypropyl ether is 50% or more.
7. The composition according to any one of claims 1 to 6, wherein the photopolymerization initiator comprises a compound represented by the following formula (1): 【Chemistry 1】 [In formula (1), R 1 represents a hydrogen atom, an optionally substituted alkyl group or an optionally substituted aryl group; X - represents a monovalent anion. 1 may be the same or different.
8. The composition according to any one of claims 1 to 7, further comprising a photosensitizer represented by the following formula (2): 【Chemistry 2】 [In formula (2), R 2 represents an alkyl group which may have a substituent. 2 may be the same or different.
9. The moisture permeability is 100 g / (m) per 100 μm of thickness measured under conditions of a temperature of 85° C. and a relative humidity of 85% in accordance with JIS Z0208. 2 The composition according to any one of claims 1 to 8, which is a composition for forming a hardened body in a curing time of 24 hours or less.
10. The composition according to any one of claims 1 to 9, which is a composition for forming a cured product having a water absorption rate of 3% or less at a temperature of 85°C and a relative humidity of 85% for 24 hours.
11. The composition according to any one of claims 1 to 10, which is a sealant for an organic electroluminescence display device.
12. The composition according to any one of claims 1 to 11, which is a sealant for forming a dam in a dam-fill system.
13. A polymerizable compound comprising at least one selected from the group consisting of an alicyclic epoxy compound and an acyclic epoxy compound; The refractive index n of the polymer of the polymerizable compound 1 The absolute value of the difference between 1 -n 2 |) is 0.5 or less, 2 At least one type of inorganic fine particles selected from the group consisting of spherical silica, spherical alumina, spherical magnesia, and spherical zirconia, A photopolymerization initiator; Contains The content of the inorganic fine particles is 30% by volume or more, The content of the photopolymerization initiator is 0.3 parts by mass or more relative to 100 parts by mass of the polymerizable compound, The composition, wherein the inorganic fine particles have an average circularity of 0.7 or more and 1.0 or less.
14. A cured product of the composition according to any one of claims 1 to 13.
15. An organic EL display element; a sealing structure including a dam and a filler for sealing the organic EL display element; Equipped with An organic electroluminescence display device, wherein the dam comprises the cured body according to claim 14 .
16. The organic EL display device according to claim 15 , which is an organic EL television.
Citation Information
Patent Citations
Composition for dental restoration
JP1987246514A
Display device
JP2001357973A
Photosensitive thermosetting paste composition
JP2004123775A
Radiation- or heat-curable barrier sealant
JP2009531515A
Curable composition
JP2015124286A